The potential acidogenicity of liquid breakfasts. (June 2016) - Byrne, Samantha J.; Tan, Kheng H.; Dashper, Stuart G.; Shen, Peiyan; Stanton, David P.; Yuan, Yi; Reynolds, Eric C.
Abstract: Objectives: To determine the potential acidogenicy of liquid breakfasts. Methods: In vitro acid production by Streptococcus mutans was measured in the beverages at a pH of 5.5, as was the fall in pH over 10 min. The buffering capacity was determined, as well as the calcium, inorganic phosphate and fluoride concentrations (total and soluble) of the beverages. Bovine milk (UHT) was used for comparison. Results: The rate of acid production by S. mutans, and pH fall over 10 min was greater in liquid breakfasts compared to bovine milk. All beverages except one demonstrated a significantly lower buffering capacity than bovine milk. All beverages contained significantly greater concentrations of soluble calcium than bovine milk, and all except two contained significantly more soluble inorganic phosphate. Conclusions: S. mutans was able to generate significantly more acid in the liquid breakfasts than in bovine milk, indicating these drinks may contribute to a cariogenic diet. In general, the liquid breakfasts required significantly less acid than bovine milk to reduce their pH to the approximate critical pH for enamel demineralisation. However, the liquid breakfasts also tended to contain significantly more soluble calcium and inorganic phosphate than bovine milk. Clinical significance: The substantial amounts and various types of sugars found within liquid breakfast beverages may result in a significant pH drop in dental plaque following consumption of these products.